Long-term Outcome in Severe Left Ventricular Primary Graft Dysfunction Post Cardiac Transplantation Supported by Early Use of Extracorporeal Membrane Oxygenation. Issue 10 (October 2020) - Connolly, Sophie; Granger, Emily; Hayward, Christopher; Huang, David; Kerr, Stephen; McCanny, Peter; Buscher, Hergen
Abstract : Background: Severe primary graft dysfunction (PGD) is the leading cause of early death following cardiac transplantation. The early use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) may facilitate graft rescue. However, the additional risks of its use are unknown. Methods: We retrospectively reviewed the medical records of all adult patients who underwent cardiac transplantation from January 2009 to February 2016 at St Vincent's Hospital, Sydney, to evaluate risk factors for the use of VA-ECMO and related morbidity and long-term survival. Results: One hundred ninety-two transplanted patients were identified, 49 (25%) of whom developed left or biventricular PGD requiring VA-ECMO. The total operation time (median 495 [interquartile range 139.8] versus 412.8 [132] min, P < 0.001), cardiopulmonary bypass time (220 [63] versus 176 [73] min, P < 0.001) and the presence of a previous sternotomy (29 [59%] versus 51 [36%], P = 0.019) were associated with the use of VA-ECMO. One-year survival in the VA-ECMO cohort was 71%. After a median follow-up time of 696 days (interquartile range 1201 d), survival was significantly higher in the non-ECMO group ( P = 0.004) but not when conditioned on hospital survival ( P = 0.34). Patients with shorter than median ECMO runtime (<108 h) had a similar long-term survival to patients who did not require ECMO ( P = 0.559). In the ECMO cohort, multivariable logistic regression revealed baseline creatinine in µmol/L (odds ratio 0.99 [95% confidence interval 0.99-1.00], P = 0.019) and duration of ECMO support in days (odds ratio 0.65 [95% confidence interval 0.44-0.97], P = 0.034) were inversely and independently associated with 1-year survival. Conclusions: Short- and long-term survival of PGD supported with VA-ECMO was better than previously described. Early recovery of PGD on VA-ECMO support negates its negative impact on short- and long-term survival.